Quality assessment of groundwater from selected sources in Barangay Malingin, Bago City, Negros Occidental - Masmila, Shiela Valdez (2006.)
The quality of groundwater from selected sources in Barangay Malingin, Bago City, negros Occidental were analyzed.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Quality assessment; Groundwater; Malingin, Bago City, Negros Occidental